SECOND ACCOUNT INSTAGRAM AS SPIRITUAL SPACES FOR URBAN SUFIS AND SELF-EXPRESSION ON SOCIAL MEDIA - Haliza, Noor; Wahdah, Nurul; Surawan, Surawan; Awang, Sarimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2025)
The existence of social demands and ideal images that must be maintained on their main Instagram accounts limits students' interactions. To express their more honest personal sides, many students choose to create second Instagram accounts as a space for freer and more authentic expression. This study aims to understand how PAI UIN Palangka Raya students use their second Instagram accounts as a means of self-expression and personal spirituality. Using a mixed method with a Sequential Explanatory design, data were collected through questionnaires (Google Form) and in-depth interviews, then analyzed using SPSS 27. The research findings show that the use of Instagram second accounts and the level of self-expression of PAI students are in the moderate category, with an average of 36.75 and 35.50, respectively. Regression analysis shows a positive and significant effect of the second account on self-expression (B = 0.585; p = 0.000), meaning that the more active students in using their second account, the higher their self-expression on social media. Behind this data, it turns out that Instagram is not only a means of social communication, but also a space for reflection in line with urban Sufism values to integrate modern life with spiritual practices. Students post spiritual reflections, prayers, and feelings that cannot be displayed on their main accounts. These findings have implications for educational institutions, particularly Islamic Education Study Programs, to take advantage of this phenomenon as an opportunity to encourage students to express religious and humanitarian values creatively on social media, while maintaining academic ethics and norms.